Peranan Kepolisian Dalam Penanggulangan Premanisme Dalam Bentuk Pemerasan Terhadap Pemilik Kios Dan Warung Di Kelurahan Liliba Kota Kupang - Sincan, Muhammad A. M; Tallo, Daud Dima; Amalo, Heryanto (Artemis Law Journal, 2025)
The role of the police in combating street crime, particularly extortion, is a crucial issue in maintaining public order and ensuring economic stability in Kupang City, Indonesia. This study focuses on the preventive and repressive measures implemented by the Kupang City Police to address extortion targeting kiosks and shop owners in Liliba Village. Using an empirical legal research method, data were collected through field observations and interviews with relevant stakeholders, including police officers and victims of extortion. The findings reveal that the Kupang City Police employ various strategies such as routine patrols, community engagement programs, and technology like CCTV to mitigate these criminal acts. Challenges faced include societal issues such as alcohol consumption, economic disparity, limited trust in law enforcement, and low legal awareness among residents. Despite these hurdles, implementing integrated law enforcement measures, supported by educational programs and technological advancements, has shown progress in reducing criminal activities. This study underscores the importance of collaboration between law enforcement agencies and the community to ensure sustainable crime prevention. Recommendations include strengthening patrols, enhancing community trust, and providing consistent legal education to effectively address societal and systemic challenges.